Gastric Cancer Regional Detection System - Ural, Berkan; Hardalac, Firat; Serhatlioglu, Selami; Ilhan, Mustafa Necmi (Springer, 2016)
In this study, a novel system was created to localize cancerous regions for stomach images which were taken with computed tomography(CT). The aim was to determine the coordinates of cancerous regions which spread in the stomach area in the color space with using this system. Also, to limit these areas with a high accuracy ratio and to feedback to the user of this system were the other objectives. This integration was performed with using energy mapping, analysis methods and multiple image processing methods and the system which was consisted from these advanced algorithms was appeared. For this work, in the range of 25-40 years and when gender discrimination was insignificant, 30 volunteer patients were chosen. During the formation of the system, to exalt the accuracy to the maximum level, 2 main stages were followed up. First, in the system, advanced image processing methods were processed between each other and obtained data were studied. Second, in the system, FFT and Log transformations were used respectively for the first two cases, then these transformations were used together for the third case. For totally three cases, energy distribution and DC energy intensity analysis were done and the performance of this system was investigated. Finally, with using the system's unique algorithms, a non-invasive method was achieved to detect the gastric cancer and when FFT and Log transformation were used together, the maximum success rate was obtained and this rate was calculated as 83,3119 %.
Keywords: Cancer; Gastric cancer; Image processing; Image acquisition; Image filtering; Image thresholding; Power Spectrum Density (PSD) analysis